Case report: Male genital system, soft tissue and myocardial metastases in a patient with exon 11-mutated GIST of unknown origin - Rota, Michele; Sganzerla, Federico; Zuffante, Michele; Mafficini, Andrea; Pavarana, Michele; Milella, Michele (Frontiers in Oncology, 2024)
Gastrointestinal stromal tumors (GISTs) are the most frequent mesenchymal tumors of the gastrointestinal tract, usually arising in the stomach or in the small bowel. Most GISTs are diagnosed early due to the presence of symptoms (e.g., abdominal discomfort/pain, anemia, etc.); at times, diagnosis could be incidental (e.g., ultrasound or endoscopic examinations performed for other reasons, surgical intervention for a different disease, etc.). Diagnosis occurs when the tumor is already metastatic in 10-20% of cases. The most common metastatic sites are liver, peritoneum, and loco-regional lymph nodes. Here, we present the case of a male patient with an atypical presentation of disease: as a matter of fact, during his oncological history, he developed metastases in unlikely sites, such as penis, scrotum, myocardium, and soft tissues.